Calculation-experimental procedure for determining welding deformations and stresses based on a digital image correlation method - Korzhyk, Volodymyr; Khaskin, Vladyslav; Savitsky, Viktor; Klochkov, Illia; Kvasnytskyi, Viktor; Perepichay, Andrii; Peleshenko, Sviatoslav; Grinyuk, Andriy; Aloshyn, Andrii; Shutkevych, Oleksii (Eastern-European Journal of Enterprise Technologies, 2022)
The object of this study is determining the stressed-strained state (SSS) of a welded article by applying quantitative non-destructive testing. The relevance of the study is associated with the need to devise a universal methodology for the non-destructive quantification of SSS using the simplest approaches and means of provision. To solve this task, an estimation-experimental procedure has been developed. This procedure is based on comparing digital stereo images of the individual sections (spatial primitives) of an article before and after its welding, followed by computer processing. To validate the developed procedure, the SSS of a cylindrical article made of aluminum alloy 7005, at the end of which two flanges were welded laserly with ring seams, was determined. It was established that after performing four diametrically opposed point tacks, the residual deformations of the ends of the article can reach 0.02–0.05 mm, and after performing continuous ring seams – to decrease to 0.01–0.02 mm. The calculation showed that the residual deformations of the end of the article after welding a ring seam are at the level of 0.02 mm, and the residual stresses in the same zone – in the range of 50–60 MPa. The deviation in the coincidence of residual deformations is in the range of 10–20 %, which is a satisfactory result and can be considered as an error in the results of determining SSS in general. Based on the developed methodology for determining SSS, an experimental industrial complex has been created that allows TIG and PAW to perform welding of objects from steels and alloys with the ability to determine the resulting stressed-strained state of these objects. The procedure devised and the equipment designed can be used for to non-destructively determine SSS of spatial structures made of steels and alloys